Socio-economic Important of Beekeeping in Lafia Local Government Area of Nasarawa State, Nigeria - , I. O. Ibrahim; , A. B. Hudu; , H. A. Ismail (Archives of Current Research International, 2022)
The study assessed the socio-economic important of beekeeping in Lafia local government area of Nasarawa state, using structured questionnaires and interview schedule. Sample of 29 respondents were selected for data collected based on the 2019/2020 production season. The data include socio-economic characteristics of the respondents, their management practices, input and output level of honey production, cost and return analysis of beekeeping in the study area. Descriptive statistics and gross margin analytical tools were utilized to analyze the data. The result revealed that majority (93.1%) of those who participated in beekeeping where males and only 6.9% were female, 69% of the respondent were married while 31.0% were singles. All the respondents 100% got their hives themselves. 100% of the respondent harvest honey, 74.4% of the respondent harvest Beeswax and other bee product for commercial purposes. The average variable cost and gross return were ₦2,927 and ₦11,152.65 respectively. The gross margin was ₦8,265.09; major constraints faced by the respondents were inadequate capital, Bee aggressiveness, theft, marketing, landownership and lack of modern equipment.